State-dependent alterations in sleep/wake architecture elicited by the M4 PAM VU0467154 – Relation to antipsychotic-like drug effects. (March 2016) - Gould, Robert W.; Nedelcovych, Michael T.; Gong, Xuewen; Tsai, Erica; Bubser, Michael; Bridges, Thomas M.; Wood, Michael R.; Duggan, Mark E.; Brandon, Nicholas J.; Dunlop, John; Wood, Michael W.; Ivarsson, Magnus; et al.
Abstract: Accumulating evidence indicates direct relationships between sleep abnormalities and the severity and prevalence of other symptom clusters in schizophrenia. Assessment of potential state-dependent alterations in sleep architecture and arousal relative to antipsychotic-like activity is critical for the development of novel antipsychotic drugs (APDs). Recently, we reported that VU0467154, a selective positive allosteric modulator (PAM) of the M4 muscarinic acetylcholine receptor (mAChR), exhibits robust APD-like and cognitive enhancing activity in rodents. However, the state-dependent effects of VU0467154 on sleep architecture and arousal have not been examined. Using polysomnography and quantitative electroencephalographic recordings from subcranial electrodes in rats, we evaluated the effects of VU0467154, in comparison with the atypical APD clozapine and the M1 /M4 -preferring mAChR agonist xanomeline. VU0467154 induced state-dependent alterations in sleep architecture and arousal including delayed Rapid Eye Movement (REM) sleep onset, increased cumulative duration of total and Non-Rapid Eye Movement (NREM) sleep, and increased arousal during waking periods. Clozapine decreased arousal during wake, increased cumulative NREM, and decreased REM sleep. In contrast, xanomeline increased time awake and arousal during wake, but reduced slow wave activity during NREM sleep. Additionally, in combination with the N -methyl-d -aspartate subtype of glutamate receptor (NMDAR) antagonist MK-801, modeling NMDAR hypofunction thought to underlie many symptoms in schizophrenia, both VU0467154 and clozapine attenuated MK-801-induced elevations in high frequency gamma power consistent with an APD-like mechanism of action. These findings suggest that selective M4 PAMs may represent a novel mechanism for treating multiple symptoms of schizophrenia, including disruptions in sleep architecture without a sedative profile. Highlights: Sleep disturbances are associated with primary symptoms in schizophrenia. Antipsychotics (APDs; clozapine) may improve sleep but cause sedation during wake. M4 muscarinic acetylcholine receptors (mAChR) represent a novel target for APDs. VU0467154 is a potent M4 mAChR positive allosteric modulator with APD-like effects. VU0467154 alters sleep like clozapine, without a sedative profile during wake.